Analysis of Quality Maturity of Polish Automotive Enterprises Using EFQM And MBNQA Models - Zbigniew WISNIEWSKI; Malgorzata WISNIEWSKA; Michal PASZKOWSKI (Communications of International Proceedings, 2021)
The article presents results of a study of 13 automotive enterprises. The research was conducted on quality maturity of these organizations. Two TQM models were used: EFQM and MBNQA. European companies implement TQM most often on the basis of experience of other European companies, therefore the universality of the WFQM model can be noticed. However, the research tool was supplemented with elements of the American approach. The American quality award model MBNQA was used for this purpose. The purpose of the research was to determine what is the awareness of managers in enterprises that declare having advanced quality systems. The results of the research were presented to the managers and met with great interest. The results made it possible to look at the organizations from a certain distance and make the companies aware of the stage of development of quality systems. Even if they have implemented the concept based on the EFQM model, the look from the MBNQA perspective allows them to notice new, interesting aspects.
Keywords: Quality management; EFQM; MBNQA